Long‐term results of combined liver‐kidney transplantation for primary hyperoxaluria type 1: The French Experience. Issue 12 (December 2014) - Compagnon, Philippe; Metzler, Philippe; Samuel, Didier; Camus, Christophe; Niaudet, Patrick; Durrbach, Antoine; Lang, Philippe; Azoulay, Daniel; Duvoux, Christophe; Bayle, Francois; Rivalan, Joseph; Merville, Pierre; et al.
<x xml:space="preserve">Abstract</x> Primary hyperoxaluria type 1 (PH1) is a hepatic metabolic defect leading to end‐stage renal failure. The posttransplant recurrence of kidney disease can suggest a need for combined liver‐kidney transplantation (LKT). However, the risk of LKT is theoretically far higher than the risk of kidney‐alone transplantation (KAT). An unselected consecutive series of 54 patients with PH1 was analyzed according to the type of transplantation initially performed between May 1979 and June 2010 at 10 French centers. The duration of dialysis, extrarenal lesions, age, and follow‐up were similar between the groups. Postoperative morbidity and mortality did not differ between the groups, and 10‐year patient survival rates were similar for the LKT (n = 33) and KAT groups (n = 21; 78% versus 70%). Kidney graft survival at 10 years was better after LKT (87% versus 13%, P < .001) . Four patients (12.1%) lost their first kidney graft in the LKT group, whereas 19 (90%) did in the KAT group (P < .001). The recurrence of oxalosis occurred in 11 renal grafts (52%) in the KAT group but in none in the LKT group (P < .001). End‐stage renal failure resulting from rejection was also higher in the KAT group (19% versus 9%, P < 0.0001). A second kidney transplant was performed for 15 patients (71%) in the KAT group versus 4 patients (12%) in the LKT group (P < 0.001). In conclusion, LKT for PH1 provides better kidney graft survival, less rejection, and similar long‐term patient survival and is not associated with an increased short‐term mortality risk. LKT must be the first‐line treatment for PH1 patients with end‐stage renal disease. Liver Transpl 20:1475‐1485, 2014. © 2014 AASLD.